La nature morte ou : Quand l’art « objecte » - Liliane Louvel (Revue LISA)
By analysing Gabriel Josipovici’s novel, Goldberg: Variations, this paper investigates the validity of a new critical perspective, namely that of applying pictorial language to the analysis of literary texts. The investigation draws on a number of critics, E. M. Forster among them, who have acknowledged the need to borrow terms from other arts to be able to “describe” certain aspects of a literary text when literary criticism is found lacking.